Proceso de elaboración, composición y producción de un single (2025)
This graduation project involved the creation, composition, and production of a single that fuses reggaetón and house, addressing creative, technical, legal, and commercial aspects. Through interviews, market analysis, financial planning, and mixing and mastering tests, a unique musical product with commercial potential was developed. The project also reflects on the challenges faced by independent artists in today's music industry.